2016
DOI: 10.1371/journal.pone.0168450
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of 2,9-Di-Sec-Butyl-1,10-Phenanthroline

Abstract: The anti-tumor effect of a chelating phen-based ligand 2,9-di-sec-butyl-1,10-phenanthroline (dsBPT) and its combination with cisplatin were examined in both lung and head and neck cancer cell lines and xenograft animal models in this study. The effects of this agent on cell cycle and apoptosis were investigated. Protein markers relevant to these mechanisms were also assessed. We found that the inhibitory effect of dsBPT on lung and head and neck cancer cell growth (IC50 ranged between 0.1–0.2 μM) was 10 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Although the selectivity index values for positive control doxorubicin have been more expressive that found for CD-CIR inclusion complexes, studies have shown that many tumors have acquired resistant to treatment with this drug. In addition, conventional drugs used in chemotherapy present various side effects as mutagenicity, teratogenicity, nephrotoxicity, neuropathy, myelosuppression, immunosuppression and cardiotoxicity [3, 4, 30]. Thus, the results obtained for the inclusion complex encouraged us to determine the activity against S-180 murine cell line in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Although the selectivity index values for positive control doxorubicin have been more expressive that found for CD-CIR inclusion complexes, studies have shown that many tumors have acquired resistant to treatment with this drug. In addition, conventional drugs used in chemotherapy present various side effects as mutagenicity, teratogenicity, nephrotoxicity, neuropathy, myelosuppression, immunosuppression and cardiotoxicity [3, 4, 30]. Thus, the results obtained for the inclusion complex encouraged us to determine the activity against S-180 murine cell line in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%